1983
DOI: 10.1111/j.1365-2125.1983.tb02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and oxazepam in the treatment of insomnia in hospitalized patients.

Abstract: Fifty‐nine hospitalized patients participated in a double‐blind study: 19 received 15 mg midazolam, 20 received 50 mg oxazepam, and 20 placebo. The three groups were comparable with regard to age, sex, height, weight, and degree and type of insomnia. The sleep‐onset latency was shorter with midazolam than with placebo or oxazepam (Mann‐ Whitney test, alpha less than 0.05). With regard to total sleep duration and the number of nocturnal awakenings, there was no difference between the midazolam and oxazepam grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The studies by Feldmeier and Kapp and Gallais et al reported a statistically significant reduction in sleep latency with midazolam (15 mg orally) compared to placebo (median difference of 30–53%, p<0.05); however, only Feldmeier and Kapp 34 found oxazepam (15 mg orally) to be superior to placebo (median difference 16%, p<0.05). Gallais et al 35 found midazolam 15 mg orally to be superior to oxazepam 50 mg orally ( table 3 ) as did Lupolover et al 36 (15 mg doses for midazolam and oxazepam), but only after 3 days of treatment ( table 3 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The studies by Feldmeier and Kapp and Gallais et al reported a statistically significant reduction in sleep latency with midazolam (15 mg orally) compared to placebo (median difference of 30–53%, p<0.05); however, only Feldmeier and Kapp 34 found oxazepam (15 mg orally) to be superior to placebo (median difference 16%, p<0.05). Gallais et al 35 found midazolam 15 mg orally to be superior to oxazepam 50 mg orally ( table 3 ) as did Lupolover et al 36 (15 mg doses for midazolam and oxazepam), but only after 3 days of treatment ( table 3 ).…”
Section: Resultsmentioning
confidence: 88%
“…Two randomised controlled trials, Feldmeier and Kapp 34 (n=50) and Gallais et al 35 (n=51), compared the effects of midazolam and oxazepam to placebo. One randomised controlled trial by Lupolover et al 36 (n=78) compared midazolam to oxazepam.…”
Section: Resultsmentioning
confidence: 99%
“…Manu studies report significant decreases in the onset of sleep and increases in duration of sleep. 25,27 There are also no remarkable hangover effects experienced in patients, as it normally is with other BZDs. 25,27 In anesthesiology, midazolam's water-soluble property is advantageous over other induction medications due to its rapid onset of action.…”
Section: Nayzilam (Midazolam) Original Usementioning
confidence: 97%
“…In recent years, however, recognition of the stage 4 suppressant effect of the benzodiazepines has led to their use, with some success, in the treatment of night terrors (Fisher et al, 1973;McLeod & Fisher, 1978). In view of these promising results, it was decided to investigate the usefulness in this indication of the new short-acting benzodiazepine midazolam which, in adult insomniacs, has been shown to be rapid in onset and very well tolerated (Gallais et al, 1983;Vogel & Vogel, 1983 (1978).…”
Section: Introductionmentioning
confidence: 99%